Research on Enhancing Adaptability in Dynamic Business Environments with Agile Project Management - Sayed, Mahmoud (Journal of Global Economy, Business and Finance, 2025)
This research paper explores the application of agile program management techniques in rapidly changing business environments. It investigates how organizations can adapt to shifting market conditions through agile principles, iterative planning, and continuous improvement. The study emphasizes the importance of flexibility, collaboration, and stakeholder engagement, highlighting the challenges and benefits of agile methodologies. The paper aims to provide practical guidance for companies seeking to navigate the complexities of swift change and ensure successful project delivery. It explores the crucial aspects of agile program management, including iterative planning, continuous improvement, and stakeholder engagement. Additionally, the research examines the pressing challenges and benefits of adopting agile methodologies, such as enhanced flexibility, improved collaboration, and advanced business outcomes. Overall, this research paper aims to provide a comprehensive understanding of the significance of agile program management in today's fast - paced business environment and offers empirical suggestions for programs seeking to leverage agile approaches for successful project delivery and outcomes.